58.5k views
3 votes
X - 4y - 1 = 0
x + 5y - 4 = 0

solve for comparison

User Dyatchenko
by
5.7k points

2 Answers

0 votes
x-4y-1=0
-x-5y-4=0
----------------
0+y+3=0
y+3-3=0-3
y=-3

Substituting y=-3 in the equation x-4y-1=0
x-4×-3-1=0
x+12-1=0
x+11-11=0-11
x=-11


User Yaniv Golan
by
7.2k points
2 votes

Answer:

(x,y) = (7/3,1/3)

Explanation:

x - 4y - 1 = 0 ------ Equation 1

x + 5y - 4 = 0 ------ Equation 2

From equation 1,

x = 4y + 1 (substitute into equation 2)

4y + 1 + 5y - 4 = 0

9y = 3

y = 1/3

Substitute into x = 4y + 1

x = 4(1/3) + 1

x = 4/3 + 1

x = 7/3

Therefore,

(x,y) = (7/3,1/3)

User Krypton
by
5.9k points